Chapter 18 USA - Ruck, Rob (Taylor & Francis, 2018)
Few issues have engaged sports scholars more than those of race and ethnicity. Today, globalization and migration mean all major sports leagues include players from around the globe, bringing into play a complex mix of racial, ethnic, cultural, political and geographical factors. These complexities have been examined from many angles by historians, sociologists, anthropologists and scientists. This is the first book to offer a comprehensive survey of the full sweep of approaches to the study of sport, race and ethnicity. The Routledge Handbook of Sport, Race and Ethnicity makes a substantial contribution to scholarship, presenting a collection of international case studies that map the most important developments in the field. Multi-disciplinary in its approach, it engages with a wide range of disciplines including history, politics, sociology, philosophy, science and gender studies. It draws upon the latest cutting-edge research to address key issues such as racism, integration, globalisation, development and management. Written by a world-class team of sports scholars, this book is essential reading for all students, researchers and policy-makers with an interest in sports studies.